Self-referencing biosensors using Fano resonance in periodic aluminium nanostructures. Issue 42 (15th September 2021) - Lo, Shu-Cheng; Yeh, Chun-Wei; Wang, Sheng-Hann; Kuo, Chia-Wen; Lee, Kuang-Li; Chern, Ruey-Lin; Wei, Pei-Kuen
Abstract : Self-referenced SPR biosensors optimized by FDTD simulation and proved by the combination of the self-referencing signals from Fano resonances of aluminum-coated nanoslit arrays which were applied in a real time multi-spectral imaging system. Abstract : Surface plasmon resonance (SPR) is an important technique for real-time and label-free detection of specific binding biomolecules. However, conventional SPR signals come from both the surface binding biomolecules and the variation in the bulk refractive index. This work demonstrates that Fano resonance in an aluminum capped nanoslit array has the ability to remove the signal of bulk refractive index changes from the SPR signal. As compared to gold nanostructures, the aluminum nanostructure provides an asymmetrical Fano resonance with clear peak and dip wavelengths. The peak wavelength is close to the grating resonance condition. The evanescent depth at the peak wavelength is up to several microns. The dip wavelength comes from the SPR effect. The evanescent depth at the dip wavelength is about 300 nm. By simultaneously measuring the shifts of peaks and the dip wavelengths, the variation in the bulk refractive index can be removed and only the biolayer thickness is measured. The finite-difference time-domain calculation shows that the 470 nm-period nanoslit array with 90 and 70 nm slit depths has the optimal thickness sensitivity. In this experiment, a simple multispectral imaging system is developed for multiple bio-interaction measurements. The measured results verify that the bulk refractive index changes can be removed and the surface biomolecular interactions can be directly obtained without the need of a reference channel.